Chronic kidney disease in patients with congenital heart disease: a nationwide, register-based cohort study. Issue 5 (2nd September 2022) - Gillesén, Mikaela; Fedchenko, Maria; Giang, Kok Wai; Dimopoulos, Konstantinos; Eriksson, Peter; Dellborg, Mikael; Mandalenakis, Zacharias
Abstract: Aims: To investigate the risk of chronic kidney disease (CKD) in young patients with congenital heart disease (CHD) (age 0–47 years) compared with age- and sex-matched controls without CHD. Methods and results: Using data from the Swedish National Patient Register and the Cause of Death Register, 71, 936 patients with CHD (50.2% male) born between 1970 and 2017 were identified. Each patient with CHD was matched by sex and age to 10 controls without CHD ( n = 714, 457). Follow-up data were collected for patients with CHD and controls until 2017. During a median follow-up of 13.5 (5.8; 25.5) years, 379 (0.5%) patients with CHD and 679 (0.1%) controls developed CKD. The risk of CKD was 6.4 times higher in patients with CHD than controls [95% confidence interval (CI): 5.65–7.27] and was highest in patients with severe non-conotruncal defects [hazard ratio (HR): 11.31; 95% CI: 7.37–17.36]. Compared with matched controls, the absolute and relative risks of CKD were greater for CHD patients born between 1997 and 2017 (HR: 9.98; 95% CI: 8.05–13.37) (incidence 39.5 per 100 000 person-years). The risk of CKD remained significantly higher after adjusting for hypertension, acute kidney injury, and diabetes mellitus (HR: 4.37; 95% CI: 3.83–5.00). Conclusion: Although the absolute risk of CKD in young patients with CHD is relatively low, patients with CHD are six times more likely to develop CKD than non-CHD controls up to the age of 47 years. Further data are needed to inform guidelines on the prevention and follow-up of CKD in CHD patients. Graphical Abstract: Graphical abstract CHD, congenital heart disease; CKD, chronic kidney disease; AKI, acute kidney injury; ht, hypertension; dm, diabetes mellitus; ICD, International Classification of Disease; HR, hazard ratio.